2019
DOI: 10.21873/anticanres.13886
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of LC3B and p62/SQSTM1 Expression in Gastric Adenocarcinoma

Abstract: Background/Aim: Autophagy is a cellular mechanism that recycles cellular components to maintain homeostasis. To investigate the clinical implication of autophagy in gastric cancer, the autophagy markers with autophagosome formation, LC3B and selective autophagy substrate p62/SQSTM1 (P62) were validated. Materials and Methods: LC3B and p62 expression was examined using immunohistochemistry, western blot assays, and reverse-transcription polymerase chain reaction (RT-PCR). The relationship of LC3B and p62 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
(26 reference statements)
1
24
0
Order By: Relevance
“…Clinicopathological studies of liver tumors have demonstrated that LC3 expression may serve as an important prognostic factor for hepatocellular carcinoma, particularly for those patients undergoing surgical resection (28). The association between increased LC3 expression and a poor prognosis in gastric cancer has been extensively studied (29)(30)(31). All these studies have indicated that LC3 may be used as an independent prognostic indicator for patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicopathological studies of liver tumors have demonstrated that LC3 expression may serve as an important prognostic factor for hepatocellular carcinoma, particularly for those patients undergoing surgical resection (28). The association between increased LC3 expression and a poor prognosis in gastric cancer has been extensively studied (29)(30)(31). All these studies have indicated that LC3 may be used as an independent prognostic indicator for patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Could be the underlying mechanism of XPO1 inhibitor activity in gastric cancer. This gives and opportunity to combine XPO1 inhibitor with various cytotoxic compounds that otherwise are not effective in generating an effective therapeutic response due to autophagy [186]. Sequestration of p62 into the nucleus may also cause sensitization to immunotherapeutic agents such as PDL1 inhibitors [186,187].…”
Section: P62mentioning
confidence: 99%
“…P62 is a ubiquitin-binding protein that is closely associated with the ubiquitination of proteins. P62 is involved in the regulation of a variety of cellular signal transduction pathways and autophagy ( 78 ). In autophagy, p62 binds to ubiquitin, forms a complex with LC3-II located on the autophagic membrane, and is degraded in the autophagic lysosome.…”
Section: Signaling Pathways In Autophagy and Tumorsmentioning
confidence: 99%